1998
DOI: 10.1093/protein/11.11.971
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the helix/strand content of globular proteins based on their primary sequences

Abstract: An improved multiple linear regression method has been proposed to predict the content of alpha-helix and beta-strand of a globular protein based on its primary sequence. The amino acid composition and the auto-correlation functions based on the hydrophobicity profile of the primary sequence have been taken into account in the algorithm. The resubstitution test shows that the average absolute errors are 0.077 and 0.073 with the standard deviations 0.059 and 0.057 for the prediction of the content of alpha-heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The L1 52/55K protein, in association with a late protein, IVa2, plays a role in encapsidation of the viral DNA (42,83,84). Some of the mRNAs initiated from the major late promoter, particularly the L1 mRNAs, contain an additional leader (i-leader) spliced together between the second and third segments of the tripartite leader (17).…”
mentioning
confidence: 99%
“…The L1 52/55K protein, in association with a late protein, IVa2, plays a role in encapsidation of the viral DNA (42,83,84). Some of the mRNAs initiated from the major late promoter, particularly the L1 mRNAs, contain an additional leader (i-leader) spliced together between the second and third segments of the tripartite leader (17).…”
mentioning
confidence: 99%
“…As one of the most efficient methods for analyzing the sequence of vector statistics, the Auto Covariance (AC) has been widely used in the prediction of secondary structure content [40,41], protein family classification by researchers [42,43], and protein interaction prediction [23]. AC variable indicates that in a given protein sequence of two residues average correlation, the expression is:…”
Section: Auto Covariancementioning
confidence: 99%
“…Regardless of its simplicity, the amino acid composition contains much important information of proteins. It is found that the amino acid composition is relevant to the structural classes (Nakashima et al, 1986;Chou, 1995), the thermal stability (Luis & Argos, 1989), the secondary structure content (Krigbaum & Knutton, 1973;Muskal & Kim, 1992;Eisenhaber et al, 1996;Zhang et al, 1996Zhang et al, , 1998a and the cellular positions (Nakashima & Nishikawa, 1994;Cedano et al, 1997). However, the amino acid composition is insu$cient to re#ect the complete information of proteins.…”
Section: Databasementioning
confidence: 99%
“…the secondary structure content, we have used the auto-correlation functions (Zhang et al, 1998a). The concept of the auto-correlation functions of a protein was probably "rst introduced by Cornette et al (1987).…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation